Lung abscess caused by Clostridium ramosum - Nanda, Neha; Voskuhl, Gene W (Journal - Oklahoma State Medical Association, 2006)
A 49-year-old male presented with weight loss and fever. Further evaluation revealed lung abscesses and Clostridium ramosum bacteremia. This is an unusual cause of infection. There have only been seven reports of infections caused by C. ramosum.